The impact of systemic administration of polyphenols on periodontitis associated with diabetes mellitus: a systematic review - Kornelija Rogalnikovaite; Auste Antipoviene; Asta Burbulyte; Egle Aida Bendoraitiene (Medical Journals Sweden, 2024)
Objective: The aim of this work was to explore the potential of polyphenol supplement consumption in enhancing the treatment of periodontitis and diabetes mellitus in both diabetic animals and humans. Materials and methods: A comprehensive search across eight databases (MEDLINE, EBSCO, Taylor & Francis, PRIMO, Web of Science, Wiley Online Library, ScienceDirect, and SAGE Journals) and two registers (ClinicalTrials.gov and Cochrane Library Trials) was conducted. Methodological quality assessment employed the Cochrane Collaboration Risk of Bias Assessment Tool for randomised controlled trials and the Systematic Review Centre for Laboratory Animal Experimentation Risk of Bias Tool for experimental animal studies. Results: Ten articles meeting inclusion criteria were identified. Three clinical studies demonstrated significant reductions in probing depth (PD) and clinical attachment loss (CAL). Ginger supplementation showed a decrease in CAL (-0.57 ± 0.50 vs. -0.14 ± 0.35, p = 0.003) and PD (-0.52 ± 0.51 vs. -0.19 ± 0.51, p = 0.04), while resveratrol supplementation exhibited a reduction in PD (-1.1 ± 0.58 vs. -0.6 ± 0.47, p < 0.001). Additionally, cranberry juice supplementation led to a decrease in PD (-0.56 ± 0.03, p < 0.001). However, there was no significant improvement in inflammation status. Although polyphenol supplementation did not impact fasting blood glucose levels, it did result in improved insulin resistance (3.66 ± 0.97 vs. 4.49 ± 1.56, p = 0.045). In diabetic animals, six studies reported a significant reduction (p < 0.05) in bone loss along with marked improvements in inflammation status. Conclusions: Despite the promising results observed in the included studies, the overall evidence supporting the positive effects of polyphenols on periodontal and diabetes mellitus status, along with their anti-inflammatory properties, remains inadequate.